2000
DOI: 10.1093/jnci/92.16.1308
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Mortality in the Mayo Lung Project: Impact of Extended Follow-up

Abstract: Extended follow-up of MLP participants did not reveal a lung cancer mortality reduction for the intervention arm. Similar mortality but better survival for individuals in the intervention arm indicates that some lesions with limited clinical relevance may have been identified in the intervention arm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
270
1
6

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 479 publications
(288 citation statements)
references
References 16 publications
11
270
1
6
Order By: Relevance
“…The current analysis did not change anyone's cause of death; hence, another mortality analysis would add nothing to what was reported recently by Marcus et al 6 Redoing the survival analysis (excluding the questionable diagnoses) would be problematic, because not all incidents were reviewed. Furthermore, survival analysis is an inappropriate outcome of a screening trial, because it is subject to lead-time bias.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The current analysis did not change anyone's cause of death; hence, another mortality analysis would add nothing to what was reported recently by Marcus et al 6 Redoing the survival analysis (excluding the questionable diagnoses) would be problematic, because not all incidents were reviewed. Furthermore, survival analysis is an inappropriate outcome of a screening trial, because it is subject to lead-time bias.…”
Section: Discussionmentioning
confidence: 82%
“…Overdiagnosis is a term that pathologists may take issue with, but it is a term used by Marcus et al 6 that has become prominent in the literature to explain the discrepancy between survival benefit in the absence of mortality benefit. For the most part, the original diagnoses were confirmed on this subset of patients, which included 105 of the original 366 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, within the category of male smokers these findings are largely representative of the community at large, since, with the exception of the prevalence screen, a sizable majority of subjects (approximately 75 percent) received their medical care outside of the Mayo Clinic (and largely outside of Minnesota, mostly in other Midwestern U. S. states). Though specific data documenting the states in which deaths occurred during active study follow-up were not available to us, additional National Death Index data collected as part of an analysis examining lung cancer mortality after active follow-up ended (in the years 1983 through 1996) [23] showed that over three quarters of deaths in study subjects occurring after 1983 took place outside Minnesota (E. Bergstralh, personal communication). Second, for a number of deaths no information was available to the mortality review committee other than the death certificate.…”
Section: Discussionmentioning
confidence: 99%
“…Early detection of disease that ultimately would not present clinically in some persons is a plausible harm of cancer screening, because it would lead to treatment, often invasive, of no clinical benefit. 1 To date, evidence suggests that "overdiagnosis" of this type is present in screening for prostate carcinoma, 2 breast carcinoma, 3 and lung carcinoma 4 and for neuroblastoma. 5 The advent of computed tomography (CT) screening raises the question of whether overdiagnosis may be clinically important for other solid organ malignancies.…”
mentioning
confidence: 99%